Competitive Landscape Of Excavator Product In Indonesia (The Indonesian Journal of Business Administration, 2021)
Infrastructure development is one of the strategic choices in enhanced development and equitable distribution of the Indonesian economy. In recent years Government has contributed to improving the quality of infrastructure in Indonesia. One type of heavy equipment that is often used for excavator is an excavator. Excavator is a heavy equipment construction equipment that has the function to do heavy work such as excavating land, collecting land, moving, transporting land and transporting goods. PT Pindad is currently developing Excavator capacity of 20 tons to meet the market demand for heavy equipment in the Infrastructure development in Indonesia, the absence of heavy equipment made in Indonesia, to reduce dependence on foreign producers and increase local content in heavy equipment domestic. The availability of heavy equipment in Indonesia is still very dependent to import product.The object of research in this final project is current condition of Excavator Market in Indonesia and marketing strategy for Excavator at PT Pindad. To solve the problem, the conceptual framework is needed to have alternative marketing strategies that are appropriate for the company.In this final project will use external and internal analysis, for external analysis using Market Overview, Consumer Analysis, PEST Analysis, Porter Five Forces Analysis and Competitor Analysis. Meanwhile, the internal analysis will use Segmenting Targeting Positioning, Marketing Mix, Resources, Capabilities, VRIO model and Value Chain Analysis. SWOT analysis is carried out to analysis the company's Strengths, Weaknesses, Opportunities and Threats. Through TOWS Analysis to get a strategy in accordance with this research.Based on TOWS strategies and analysis mentioned before, author choose of strategy Product development of variant excavator as the biggest heavy equipment business so PT Pindad will develop excavator products for excavator variants in addition to the 20 ton type excavators.Keywords: Infrastructure, Excavator, Marketing